Post-Divorce Copyright Legal Status: An Indonesian Legal Perspective - Zahry, Ariel Alvi; Fidhayanti, Dwi; binti Muhammad Jebat, Damia Batrisyia (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Decision Number 1622/PDT.G/2023/PA.JB is a new precedent for the world of Indonesian law in the future, especially regarding copyright in the context of divorce because it raises problems related to the distribution of economic rights after divorce that arise over copyrighted works. This research aims to determine the position of work objects created during marriage and the status of economic rights to work objects after divorce. The research method used in this research is normative juridical with a statutory and regulatory approach. Primary and secondary legal materials are obtained through literature studies and explained using grammatical and extensive legal interpretation. The research results show that the position of created objects owned during marriage can be considered joint property, with the emphasis on the principle of togetherness in the marital relationship. Referring to Article 37 of Law no. 1 of 1974 and Article 97 of the Compilation of Islamic Law, the economic rights status of post-divorce copyrights which become joint property can be transferred, either in whole or in part for certain reasons. Therefore, the division of copyright after divorce needs to consider the contribution of each party in creating the work as well as the economic value of the copyrighted work itself. This research provides an important contribution in understanding the position of creative works as intangible assets in marriage and their impact on the division of joint assets after divorce.